Pengaruh Rasio Laporan Keuangan terhadap Kebijakan Penyaluran Kredit pada Bank Perkreditan Rakyat Konvensional di Indonesit - Inayah Adi Sari; Makmur Sujarwo (Faculty of Economics and Business, University of Pancasakti Tegal, 2017)
Loan portfolio is the main activity in the banking sector. These activities generate revenue so that banks in carrying out its functions should be based on the precautionary principle. It is necessary to pay attention to factors such as the ratio of credit loans (NPL), factor capital adequacy ratio (CAR and DPK), the level of the operational efficiency of the bank (BOPO) and the level of profit generated (ROA) . reseach was done in order to determine the effect the relationship between the variables ( NPL, CAR, DPK, ROA and ROA) on the variable number of loans at BPR Konventinal in Indonesia. The method used is quantitative method. This study used cross section data in 2014 -2016 were obtained through an annual financial report on the official website of the financial services authority. This study using purposive sampling method. based on the criteria, there were 41 BPR sampled. Hypothesis testing is done by using multiple linear regression and classic assumptions. T test results showed that the variables NPL significant negative effect on the amount of lending. While the variable CAR, deposits and ROA positive and significant impact on the amount of lending and ROA has no effect on the amount of lending. Based on F test showed that the variables NPL, CAR, DPK, ROA and ROA simultaneously affect the amount of lending. The coefficient of determination shows that the predictive ability of the independent variables fifth by 82% while the remaining 18% are influenced by other variables outside the research